Streptococcus salivarius Prosthetic Joint Infection following Dental Cleaning despite Antibiotic Prophylaxis - Lyra B. Olson; Daniel J. Turner; Gary M. Cox; Christopher J. Hostler (Case Reports in Infectious Diseases)
We present the case of a 92-year-old man with septic arthritis of a prosthetic hip joint due to Streptococcus salivarius one week following a high-risk dental procedure despite preprocedure amoxicillin. S. salivarius is a commensal bacterium of the human oral mucosa that is an uncommon cause of bacteremia. S. salivarius has previously been described as a causative agent of infective endocarditis and spontaneous bacterial peritonitis but was only recently recognized as a cause of prosthetic joint infection. This case highlights the potential pathogenicity of a common commensal bacteria and the questionable utility of prophylactic antibiotics before dental procedures to prevent periprosthetic joint infections.